2002
DOI: 10.1023/a:1015704827984
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of our study was to demonstrate impaired allocation of processing resources in non-demented patients with early-stage mild Parkinson's disease (PD) using a multimodal event-related potential (ERP) paradigm. The multimodal ERP paradigm was performed in 18 non-demented medicated patients with early-stage PD (Mini-Mental State Examination Score >26) and 16 matched normal controls, the Global Field Power (GFP) was employed for ERP components analysis, and the new modified Wisconsin Card Sorting Test (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 60 publications
1
2
1
Order By: Relevance
“…Surprisingly, the P3a component trended towards being larger in the PD group than the CTL group at the FCz electrode (ON vs. CTL: t(48)=1.90, p=.06; OFF vs. CTL: t(48)=1.56, p=.13), in contrast to some previous findings of a diminished P3a (Polich, 2007; Solís-Vivanco et al, 2015; Tsuchiya et al, 2000; Zeng et al, 2002). However, this small component is riding on top of a larger underlying trend; high-pass filtering the data at 1 Hz (as in Solís-Vivanco et al, 2015) removes this shift and reverses these trends (ON vs. CTL: t(48)=−.25, p=.81, OFF vs. CTL t(48)=−.75, p=.46).…”
Section: Resultscontrasting
confidence: 93%
See 2 more Smart Citations
“…Surprisingly, the P3a component trended towards being larger in the PD group than the CTL group at the FCz electrode (ON vs. CTL: t(48)=1.90, p=.06; OFF vs. CTL: t(48)=1.56, p=.13), in contrast to some previous findings of a diminished P3a (Polich, 2007; Solís-Vivanco et al, 2015; Tsuchiya et al, 2000; Zeng et al, 2002). However, this small component is riding on top of a larger underlying trend; high-pass filtering the data at 1 Hz (as in Solís-Vivanco et al, 2015) removes this shift and reverses these trends (ON vs. CTL: t(48)=−.25, p=.81, OFF vs. CTL t(48)=−.75, p=.46).…”
Section: Resultscontrasting
confidence: 93%
“…While previous studies have found reduced P3a amplitudes in individuals with Parkinson’s disease (Polich, 2007; Tsuchiya et al, 2000; Zeng et al, 2002), the evidence is somewhat mixed across studies (Seer et al, 2016). We demonstrate here that signal processing choices (e.g.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Indeed, past work has found that N2 and ERN amplitudes are diminished in non-demented PD patients, analogous to this study (Seer et al, 2016; Seer et al, 2017), as are P3a amplitudes (Polich, 2007; Solis-Vivanco et al, 2015; Tsuchiya et al, 2000; Zeng et al, 2002). Taken together, these findings suggest a common deficit in the mid-frontal mechanisms that signal the need for cognitive control.…”
Section: Discussionsupporting
confidence: 86%